Resolving active species during the carbon monoxide oxidation over Pt(111) on the microsecond timescale - Calley N. Eads; Weijia Wang; Ulrike Küst; Julia Prumbs; Robert H. Temperton; Mattia Scardamaglia; Joachim Schnadt; Jan Knudsen; Andrey Shavorskiy (Nature Communications)
Abstract Catalytic studies traditionally rely on steady-state conditions resulting in time-averaged datasets that do not differentiate between active and spectator species. This limitation can cause misinterpretations of catalytic function, as the signal of short-lived intermediates responsible for producing desired reaction products is often masked by more intense spectator species. Time-resolved ambient pressure X-ray photoelectron spectroscopy (tr-APXPS) mitigates this issue by combining microsecond time resolution under reaction conditions. Using tr-APXPS, we investigate the oxidation of CO over Pt(111) by concurrently tracking reaction products, surface intermediates, and catalyst response. Our findings reveal that chemisorbed oxygen, rather than Pt surface oxide, is the main species reacting with CO to form CO2, supporting a primary Langmuir-Hinshelwood mechanism. The results shed new light on a heavily-debated reaction in catalysis. Beyond using CO pulses to determine active species, we demonstrate how careful tuning of pulsing parameters can be used for dynamic catalyst operation to enhance CO2 formation.